Effect of High Protein Diet Containing Fortified Bread with Fenugreek and Nigella sativa Seeds on Rats Suffering from Diabetes - Mahmoud, Mohamed Y. (Pakistan Journal of Nutrition, 2013)
The present work was conducted to study the effect of high protein diet containing fortified bread with two levels from fenugreek seeds (FS), Nigella sativa seeds (NSS) and combination of them on the nutritional value, percent of liver weight/body weight, lipid parameters, kidney and liver functions, serum glucose and thyroid hormones of rats suffering from diabetes. Sixty male albino rats (150-165 g) were used in this study. After a period of adaptation the rats were divided into two main groups. The first main group (12 rats) divided into two subgroups (n = 6), these subgroups were fed on normal and high protein diets (14 and 20% protein) containing 250 g un-fortified bread, respectively, as control negative groups. While the second main group (48 rats) was injected with alloxane (150 mg/ kg body weight) to induce hyperglycemia. The second main group divided into eight subgroups (n = 6), subgroups (1 and 2) fed on normal and high protein diets containing 250 g un-fortified bread, as a positive control groups. Subgroups (3 and 4) fed on high protein diets containing 250 g bread fortified with 5 and 10% FS, respectively. Subgroups (5 and 6) fed on high protein diets containing 250 g bread fortified with 5 and 10% NSS, respectively. The last subgroups (7 and 8) fed on high protein diets containing 250 g bread fortified with (5% FS and 5% NSS) and (10% FS and 10% NSS), respectively. Addition fortified bread with FS, NSS and combination of them to high protein diets decreased feed intake and body weight gain%, these treatments decreased the percent liver weight/ body weight, serum cholesterol, triglycerides, low-density lipoprotein cholesterol (LDL-c), very low-density lipoprotein (VLDL-c), uric acid, urea nitrogen, creatinine, aspartate amino transferase (AST) and alanine amino transferase (ALT), alkaline phosphatase, serum glucose, as compared to the positive control groups, while high-density lipoprotein (HDL-c), T3 and T4 increased. It was concluded that, treating diabetic rats with high protein diet containing fortified bread with (10% FS and 10% NSS) realized the best effect on serum glucose, lipid profile, thyroid hormones, kidney and liver functions, followed by the groups which treated with fortified bread with high levels from FS and NSS.